Factors Associated With the Management of Adverse Drug Reactions Among Community Pharmacists in South Korea. Issue 2 (June 2019) - Ha, Dongmun; Song, Inmyung; Park, Sunyoung; Lee, Eui-Kyung
Abstract : Objectives: Community pharmacists dispensed 68.4% of all drugs used in Korea, but reported only 2.0% of adverse drug reactions (ADRs) in 2011. This study compared community pharmacists' understanding of the importance of ADR management and their actual practice of it, and identified relevant factors related to their management of ADR. Methods: With the use of a modified health belief model (HBM), 800 community pharmacists were surveyed via social network service messaging. A total of 200 usable responses were obtained for an effective response rate of 25.0%. Descriptive analysis was used to quantify the differences between community pharmacists' understanding of the importance of ADR prevention and their practice. A hierarchical regression was performed with the following predictors: (1) demographic factors, (2) social impact of ADR prevention, (3) importance of social support, and (4) cognition about the importance of ADR prevention. Results: Although community pharmacists clearly recognized the importance of ADR management, their performance was very low. The disparity between cognition and performance was more pronounced for ADR reporting than for patient counseling. Social support was the most powerful predictor of ADR prevention practice, explaining 18.5% of the variance in ADR prevention practice. Social impact of ADR prevention, demographic factors, and cognition about the importance of ADR prevention explained 12.6%, 6.2%, and 1.8% of the variance, respectively. Conclusions: Strengthening community pharmacists' performance of population-based ADR management should be prioritized over patient-oriented ADR management. To improve public health, community pharmacists should make an effort at ADR reporting. This can be done with appropriate government support, such as incentives to community pharmacists, public awareness campaigns, education, and establishment of feedback systems.